Markt und Staat in einer globalisierten Wirtschaft Japanisch-deutsches Symposium in Kyoto vom 18. bis 20. September 2008 - Kitagawa, Zentaro; Assmann, Heinz-Dieter; Nettesheim, Martin; Kansaku, Hiruyuki; Isomura, Tamotsu (Mohr Siebeck, 2010)
The articles in this volume describe how Japan and Germany approach the problems resulting from internationalization and globalization by shifting the boundaries between the market, competition and contractual regulation on the one hand and sovereign-governmental control on the other hand.
PublicationDate: 20240123
Keywords: Rechtsvergleichung -- Japan -- Japanisches Recht -- Ordnung der Wirtschaft -- Internationalisie -- Internationales Privatrecht